Economic development of Czech Republic in 2004-2013 in the aspect of foreign capital and quality of entrepreneurship environment - I. I. Bolotov (Russian Journal of Economics and Law)
Objective: to estimate the long-term development of Czech Republic after its joining the Europeоn Union (in 2004-2013), in the aspect of foreign capital and quality of entrepreneurship environment in the best developed region - Prague. Methods: macroeconomic development is viewed with the model of K. Schiller - N. Kaldor “magic” quadrangle. To evaluate the quality of entrepreneurial environment, the regression analysis of time series was used. The article uses the data of the Czech Statistical Agency ČSÚ, the European Union Statistics Agency Eurostat and the World Bank report Doing Business 2004-2014. TheregionaldataarepresentedwithЕСNUTS2technique. Results: The Czech Republic as one of the most developed economies of Central and Eastern Europe is ahead in terms of economic indicators of the average value for the EU and its new member states. The long-term problems of the country include the budget deficit and the consequences of the 2012-2013 recession. Compared with other capitals of the new EU member states, Prague is a successful city from the point of view of the investment climate, without considering a number of deficit budgets in recent years. Scientific novelty: The article analyzes the development of the Czech economy with the main macroeconomic indicators, as well as the investment attractiveness and competitiveness of Prague. This article, according to the author, is the first research on this topic published in Russian. Practical value: The possibility to better understand the Central and Eastern European economy on the example of the Czech Republic economy.